Detection of minimal residual disease in childhood acute lymphoblastic leukemia: technology and clinical applications - Pawlowska, Anna B. (Contemporary Oncology/Współczesna Onkologia, 2005)
At the time of achieving clinical remission, patients with acute lymphoblastic leukemia (ALL) may harbor up to 10 10 residual leukemic blasts. Detection of these cells is beyond the sensitivity level of classical cytomorphologic methods; they represent Minimal Residual Disease (MRD). Sensitive techniques developed for MRD detection can better define the leukemic burden and detect the residual blasts at the 0.1-0.0001% level. The most promising techniques for MRD monitoring are flow cytometric detection of aberrant immunophenotypes and polymerase chain reaction analysis of clonal antigen-receptor gene rearrangements. These techniques allow monitoring of MRD in almost all patients with pediatric ALL (up to 95%). In published clinical trials, MRD detection proved to be an excellent prognostic factor in the outcome of children with ALL. Evaluation of early treatment response allows for precise risk stratification that may lead to the tailoring of the treatment intensity and the reduction of long-term toxicities. Additionally, the detection of an increase in the MRD level enables one to anticipate an impending relapse. In this review, I discuss techniques used for MRD detection as well as the prognostic value of MRD monitoring during front-line treatment of childhood leukemia, during treatment of relapsed disease, and prior to bone marrow transplantation for ALL.